2013
DOI: 10.1074/jbc.m113.492066
|View full text |Cite
|
Sign up to set email alerts
|

Centrosomal Protein DZIP1 Regulates Hedgehog Signaling by Promoting Cytoplasmic Retention of Transcription Factor GLI3 and Affecting Ciliogenesis

Abstract: Background: All known cilia-related proteins regulate Hedgehog signaling through their role in ciliogenesis. Results: The centrosomal protein DZIP1 interacts with and sequesters GLI3 transcription factor in the cytoplasm and also regulates ciliogenesis. Conclusion: DZIP1 is the first known cilia-related protein that regulates Hedgehog signaling through a dual mechanism. Significance: Understanding how DZIP1 regulates Hedgehog signaling provides new insights into the molecular mechanism of Hedgehog signal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 48 publications
(46 reference statements)
2
55
0
Order By: Relevance
“…Interestingly, cilium-related proteins such as tubulin family members and DZIP1/Iguana were specifically purified with TAP-Cby1. DZIP1 has been shown to localize to mother centrioles and to play an essential role in primary cilium formation (38)(39)(40). It also binds to the Gli3 transcription factor to regulate Hedgehog signaling (38)(39)(40).…”
Section: Identification Of Fam92a As a Cby1-interacting Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, cilium-related proteins such as tubulin family members and DZIP1/Iguana were specifically purified with TAP-Cby1. DZIP1 has been shown to localize to mother centrioles and to play an essential role in primary cilium formation (38)(39)(40). It also binds to the Gli3 transcription factor to regulate Hedgehog signaling (38)(39)(40).…”
Section: Identification Of Fam92a As a Cby1-interacting Proteinmentioning
confidence: 99%
“…DZIP1 has been shown to localize to mother centrioles and to play an essential role in primary cilium formation (38)(39)(40). It also binds to the Gli3 transcription factor to regulate Hedgehog signaling (38)(39)(40). Further inspection of the list led us to focus on FAM92A for the following reasons: (i) its role in ciliogenesis is unknown; (ii) it contains a putative lipid-binding BAR domain, which is consistent with the localization and functional association of Cby1 with membranes (6); and (iii) it colocalizes with Cby1 at mother centrioles (see Fig.…”
Section: Identification Of Fam92a As a Cby1-interacting Proteinmentioning
confidence: 99%
“…Fish with a Dzip1/iguana mutation develop an abnormal midline and body shape (9,10) with defects in the Hedgehog (Hh) signaling pathway (8,11). Dzip1 is also involved in Hh signaling in mice (12) by regulating the turnover of Gli proteins (12)(13)(14). In addition to its role in the regulation of Hh signaling, Dzip1 is also required for ciliogenesis in zebrafish Kupffer's vesicle cells (15,16) and in cultured mammalian cells (12,17,18).…”
mentioning
confidence: 99%
“…Previous studies in cultured human cells suggested a redundant role for DZIP1 and DZIP1L in ciliogenesis 17 , a conclusion supported by our zebrafish in vivo experiments (data not shown). DZIP1 localizes to the basal body, the transition zone, and mother centriole 22,43 . Our findings reveal a similar localization pattern for DZIP1L, and proteomic studies in Chlamydomonas reinhardtii further support DZIP1L as a transition zone protein 44 .…”
Section: Discussionmentioning
confidence: 99%
“…2), and previous overexpression studies showed localization to the ciliary base 17 . In zebrafish and mice, we and others have implicated the paralogue Dzip1 in hedgehog (HH) signalling and ciliogenesis [18][19][20][21][22] , but there is little known about Dzip1l function in any organism.…”
Section: Dzip1l Is a New Arpkd Genementioning
confidence: 99%